Open Sourcing Proprietary Application Case Study: KIRI Website - Pascal Alfadian Nugroho; Vania Natali (Universitas Multimedia Nusantara, 2017)
KIRI, a previously closed source project, is a web-based public transport navigation application that serves Bandung and other cities in Indonesia. It was originally made for commercial purpose, but relatively unsuccessful. Rather than shutting it down, we transformed KIRI to an open source project. In this paper we explain such process of transformation. First, we identified technical infrastructures required by an open source project by literature review. Then, we surveyed various existing open source projects in Indonesia in terms of their completeness in technical infrastructure. Based on findings from literature review and survey, we converted KIRI into an open source project. Finally, we checked final result of this transformation, to ensure everything worked well. There were some problems found after conversion, and had been fixed accordingly. Further research is needed to see if the open sourced KIRI can attract community participation.